Insight into the physical and chemical attributes of polypropylene microplastics / Nor Ku Nazatul Husna Mohd Jackariya ... [et al.] - Mohd Jackariya, Nor Ku Nazatul Husna; Abdul Wahab, Nor Aimi; Isa, Norain; Othman, Norfaezatul Alysa; Zamri, Nor Ayuni; Inderan, Vicinisvarri (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
Microplastics (MPs) are increasingly recognised for their significant impact on the environment and human health. Understanding MPs is crucial to grasp their widespread presence in various environmental areas. The unique properties of MPs, such as their small size, durability, and potential to adsorb and transport environmental pollutants, underscore the necessity of studying their characteristics. This study aims to investigate the physical and chemical characteristics of polypropylene microplastics (PPMPs) and address the dispersion stability issues associated with them. The PPMPs were characterised using scanning electron microscopy (SEM), revealing a surface structure marked by cracks, fractures, and a rough texture. The PPMPs were observed as irregularly shaped, white particles. Their size distribution spans from 14 to 96 μm, with a mean size of 50.00 μm. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of polypropylene functional groups, specifically identifying characteristic peaks at 2952-2846 cm-1 and 1456 -1376 cm-1, indicating C-H stretching and bending vibrations, respectively, with additional peaks suggesting degradation. The effect of different concentrations of sodium lauryl sulfate (SLS) on PPMPs dispersion indicated that 5% SLS led to superior dispersion of PPMPs, thereby addressing the stability issue. These findings provide comprehensive insights into the physical and chemical attributes of PPMPs and their dispersion stability, offering a foundation for informed environmental assessments and the development of effective mitigation strategies.